Sophisticated Gene Regulation for a Complex Physiological System: The Role of Non-coding RNAs in Photoreceptor Cells - Carrella, Sabrina; Banfi, Sandro; Karali, Marianthi (Frontiers in Cell and Developmental Biology, 2021)
Photoreceptors (PRs) are specialized neuroepithelial cells of the retina responsible for sensory transduction of light stimuli. In the highly structured vertebrate retina, PRs have a highly polarized modular structure to accommodate the demanding processes of phototransduction and the visual cycle. Because of their function, PRs are exposed to continuous cellular stress. PRs are therefore under pressure to maintain their function in defiance of constant environmental perturbation, besides being part of a highly sophisticated developmental process. All this translates into the need for tightly regulated and responsive molecular mechanisms that can reinforce transcriptional programs. It is commonly accepted that regulatory non-coding RNAs (ncRNAs), and in particular microRNAs (miRNAs), are not only involved but indeed central in conferring robustness and accuracy to developmental and physiological processes. Here we integrate recent findings on the role of regulatory ncRNAs (e.g. miRNAs, lncRNAs, circular RNAs, antisense RNAs), and of their contribution to PR pathophysiology. We also outline the therapeutic implications of translational studies that harness ncRNAs to prevent PR degeneration and promote their survival and function.